AGGRESSIVE ATTITUDES AND PREVALENCE OF BULLYING BYSTANDER BEHAVIOR IN MIDDLE SCHOOL. Issue 8 (25th July 2016) - Datta, Pooja; Cornell, Dewey; Huang, Francis
Abstract : Separate lines of research find that proaggressive attitudes promote peer aggression and that bystanders play a pivotal role in deterring or facilitating bullying behavior. The current study hypothesized that proaggressive attitudes in middle school would deter students from standing up to bullying and encourage them to reinforce bullying behavior. Middle school students ( n = 28, 765) in 423 schools completed a statewide school climate survey that included an aggressive attitudes scale and their bystander response to a recent episode of bullying, which was categorized as upstanding, reinforcing, or passive. Multilevel logistic regressions indicated that higher aggressive attitudes were associated with less upstanding behavior at the school level and less upstanding behavior and more reinforcing behavior at the individual level, while controlling for other school and student demographic variables. These findings suggest that antibullying programs might address student attitudes toward aggression as a means of boosting positive bystander intervention.